Illusionary adaptive support as a means for intrinsic motivation in CSCL settings: A case in concept mapping - Hadjileontiadou, Sofia; Nikolaidou, Georgia; Hadjileontiadis, Leontios (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
The purpose of the present study was to examine if the provision of illusionary adaptive support, in the form of control that resides at the collaborators, could be perceived as such and cause intrinsic motivation towards better collaboration in Computer Supported Collaborative Learning (CSCL) settings. A pilot study on a case of collaborative concept mapping from four dyads was conducted. The preliminary results showed that the two experimental dyads, who received this type of support, produced richer concept maps and better collaborative performance, as compared to the two control ones who did not receive it. The proposed approach extends previous relative work from individual to collaborative settings and reveals new possibilities in the design of adaptive CSCL support.